2018
DOI: 10.1016/j.comppsych.2018.01.009
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing gender differences in nonsuicidal self-injury: Evidence from a large clinical sample of adolescents and adults

Abstract: While nonsuicidal self-injury (NSSI) is common in both men and women, research exploring the intersection of NSSI and gender has been limited by the use of small samples of males drawn primarily from non-clinical populations. To address these limitations, we analyzed data from a large sample of patients enrolled in an NSSI partial hospitalization program (PHP) to compare males and females across several variables, including NSSI characteristics, correlates, and pre-post treatment outcomes. Results indicated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 45 publications
6
51
0
9
Order By: Relevance
“…This raises the question of whether self-harming males are less prone to seeking help from the health care system and/or if they are adequately assessed for self-harm. It has also been suggested that males may present with a different clinical picture, including lower reported severity levels of self-harm correlates [23]. Self-harm has a history of being thought of as a problem mainly affecting females [24], but reporting levels may also be influenced by perceived stigma [25,26] as well as professional bias based on assumptions of sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether self-harming males are less prone to seeking help from the health care system and/or if they are adequately assessed for self-harm. It has also been suggested that males may present with a different clinical picture, including lower reported severity levels of self-harm correlates [23]. Self-harm has a history of being thought of as a problem mainly affecting females [24], but reporting levels may also be influenced by perceived stigma [25,26] as well as professional bias based on assumptions of sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Possible sex differences in the ideation-to-action transition might pertain in part to differing uses and features of NSSI in autistic men and women, which have not been addressed by previous studies of NSSI in autistic adults without intellectual disability [35,40]. In non-autistic samples, there are some differences in the features of NSSI (for instance, wallpunching being a more common and often underrecognized form of self-injury in men [96], and cutting being more common in women [97]), and in the functional purpose of self-injury (with men less likely to use NSSI to influence others or avoid interacting with people [98], though others contradict this [4]). Sex differences in autistic NSSI, suicide, and the ideation-action transition are certainly a worthy line of enquiry.…”
Section: Limitations and Directions For Future Studymentioning
confidence: 96%
“…6,7 It was reported that 20% of psychiatric patients engage in NSSI, while 5.5% of the community population experience the problem. 3,8 Accumulated findings suggest that NSSI is associated with severe psychopathologies including depressive disorders, anxiety disorders, personality disorders, eating disorders and substance use disorders [9][10][11] thereby highlighting the importance of research on NSSI among clinical populations.…”
Section: Introductionmentioning
confidence: 99%